The Role of Islamic Corporate Governance and Risk toward Islamic Banks Performance: Evidence from Indonesia - Emile Satia Darma; Akhsyim Afandi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: This study aims to analyze the role of Islamic corporate governance mechanisms on the performance of Islamic banks. Besides, it also analyzes the effect of risk profiles, especially those that are directly related to bank financing, on the performance of Islamic banks.Design/Methodology/Approach: Islamic banks that become the objects are Sharia Commercial Banks (SCB) and Sharia Business Units of Conventional Banks (SBU). This study uses data from 20 Islamic banks (11 SCB and 9 SBU). The analytical tool used in this study is panel data regression.Research findings: The results show that the meeting frequency of the Board of Commissioners (BC), Sharia Supervisory Board (SSB), Financing to Deposits Ratio (FDR), and bank size have a significant positive effect on the performance of Islamic banks. Non-Performing Financing (NPF) has a significant negative effect on the performance of Islamic banks.Theoretical contribution/Originality: This study utilized Stakeholders theory, Maqashid Sharia concept, and corporate governance to investigate the role of Islamic corporate governance mechanisms and risk management on Islamic banks performance.Practitioner/Policy implication: The implication of this study is that SSB activities had a direct and robust influence on Islamic banks, which have relatively larger assets. Hence, the task of the Sharia Supervisory Board should not be limited to only monitoring the conformity of transactions with sharia but also providing input so that banks can increase their profits in line with sharia.Research limitation/Implication: The limitation in this study is the number of corporate governance variables that was limited.